Implementasi Green Design dengan Konsep Nature pada Perancangan Interior Green Product Centre di Surabaya - Fransisca, The (Intra, 2013)
Global warming is one of thephenomenon forms due today environmental problems,so that green design as an answer to respond environmental issues and human inside. Embodiment of green design into a building are important, but people still lack awareness of it. Therefore, we need a place that is environmentally friendly, educating, and can transmit eco friendly lifestyle for the public.This interior design implementing green design aspects with the facilities such as galleries, workshop, consultation area, office, cashier, and receptionist with the application of nature as the conceptthat has the character which is purity, diversity, dynamic, and openness. Green design aspects with the concept of nature is applied to the layout arrangement, natural colors, diversity of shapes for the furniture and elements of interior, eco friendly materials, lighting, and energy efficiency ventilation. Design method used is analysis method. Through this design,can provide a Green Product Centre interior designthat environmentally friendly, educating, and can improve the eco friendly lifestyle for the whole community.